Tregs and infections: on the potential value of modifying their function - Sehrawat, Sharvan (Society for Leukocyte Biology, 2011)
CD4(+) T cells, which express a master transcription factor, Foxp3, have been recognized as bona fide Tregs. These cells are essential to maintain immune homeostasis in healthy as well as infected mice and humans. Extensive investigations in the last decade have provided ways to manipulate the Foxp3(+) Treg response therapeutically so the role of such cells in microbe-induced inflammatory reactions can be evaluated. This review focuses on our current understanding of the mechanisms required for the generation and sustenance of Tregs in vivo and the potential value of modulating Tregs to control microbe-induced immunopathological responses.